Identificação de elementos para avaliar o desempenho de revendedores autorizados de móveis planejados - Luz, Gilberto Barbosa da (Universidade do Vale do Rio do Sinos, 2008)
Resale channels are a competitive strategy that companies use to improve and consolidate their consumer market. Adopting resale channels is a practice of business management that can improve the success of a corporation, especially because it enlarges its range of acting. At the same time, adopting resale channels can cause different trouble to the corporation. Authorized resale, even being representative of a trade mark, is appointed by legal enterprises other than the corporation of origin. This fact allows the resale channel to act in a different way from what the original politics predicts and produces negative results in its service for certain markets. If someone resells to carry out an ineffective or inefficient acting, the damage will not be only for the authorized resale, but also for the corporation that owns the mark, as the final consumer possibly does not differentiate the inefficiency of the resale from the inefficiency of the mark or product what the resale represents. Identifying elements that
Keywords: grupo focado; relacionamento entre fabricante e revenda autorizada; elementos para avaliação de desempenho; focus group; relationship between corporation and resale; survey; elements for performance evaluation; Engenharias